The optimal lifetime of capital goods and pricing policies for replacement components and repair costs - Stepan, Adolf; Hillinger, Christian
The relationship between purchase price and repair costs is demonstrated as playing an important part in determining the economically optimum life-span of a capital good : the study is based on commercial aircraft.
Cash flows generated by capital goods with components subject to wear and tear generally show an irregular pattern of cost impulses. Under special circumstances-with given utilization rates and standardized mean times between removals (as in the case of commercial aircraft)-cash flows reveal periodic cost impulses. We use this insight first to present a new approach in lifetime organization, and then to compute the optimal lifetime for a commercial aircraft. We show the sensitivity of optimal lifetime with respect to changes in the prices of principal components and in discount rates. It can therefore be demonstrated that there is an interesting interaction between pricing policies for components on the other hand and optimal lifetime estimates and salvage values on the other.
Keywords: Capital goods; Pricing policies; Replacement components; Repair costs